Exchange rates, retailers, and importing: Theory and firm-level evidence - Patrick Alexander; Alex Chernoff (Bank of Canada, 2019)
We develop a model with firm heterogeneity in importing and cross-border shopping among consumers. Exchange-rate appreciations lower the cost of imported goods, but also lead to more cross-border shopping; hence, the net impact on aggregate retail prices and sales is ambiguous. Using Canadian firm-level data from 2002 to 2012, we find empirical support for several predictions of the model. We then estimate the model-implied exchange-rate elasticities of aggregate retail prices and sales. Our benchmark results indicate a deflationary effect of appreciations on retail prices and a small positive effect on sales. From 2002 to 2012, the Canadian exchange rate appreciated by 57%, which, according to our model, led to a 6.5% reduction in the retail price index. We also find that the estimated elasticities of aggregate retail prices and sales grew over this period, driven by import growth from China. This suggests that the transmission of exchange-rate movements to prices has grown since the early 2000s, which has consequences for the role of Canada's flexible exchange rate regime in supporting inflation stability.
Keywords: F10; F14; L81; 330; Exchange rates; International topics; Service sector